х = 2,5; у = 12,8; b - ?
у = 4х + b
b = у - 4х
b = 12,8 - 4 · 2,5
b = 12,8 - 10
b = 2,8
3 целых 1 / 8 + 1 целая 3 / 4 ) × Х = 2 целых 1 / 6
( ( 3 * 8 + 1 ) / 8 + ( 1 * 4 + 3 ) / 4 ) * х = ( 2 * 6 + 1 ) / 6
( ( 24 + 1 ) / 8 + ( 4 + 3 ) / 4 ) * х = ( 12 + 1 ) / 6
( 25 / 8 + 7 / 4 ) * х = 13 / 6
( 25 / 8 + 7 * 2 / ( 4 * 2 ) ) * х = 13 / 6
( 25 / 8 + 14 / 8 ) * х = 13 / 6
39 / 8 * х = 13 / 6
39 * х * 6 = 8 * 13
х = 8 * 13 / ( 39 * 6 )
х = 2 * 4 * 13 / ( 13 * 3 * 2 * 3 )
Числитель и знаменатель в дроби сокращаем на 13 и 2, тогда
х =1 * 4 * 1 / ( 1 * 3 * 1 * 3 )
х = 4 / ( 3 * 3 )
х = 4 / 9
ответ: х = 4 /
3 целых 1 / 8 + 1 целая 3 / 4 ) × Х = 2 целых 1 / 6
( ( 3 * 8 + 1 ) / 8 + ( 1 * 4 + 3 ) / 4 ) * х = ( 2 * 6 + 1 ) / 6
( ( 24 + 1 ) / 8 + ( 4 + 3 ) / 4 ) * х = ( 12 + 1 ) / 6
( 25 / 8 + 7 / 4 ) * х = 13 / 6
( 25 / 8 + 7 * 2 / ( 4 * 2 ) ) * х = 13 / 6
( 25 / 8 + 14 / 8 ) * х = 13 / 6
39 / 8 * х = 13 / 6
39 * х * 6 = 8 * 13
х = 8 * 13 / ( 39 * 6 )
х = 2 * 4 * 13 / ( 13 * 3 * 2 * 3 )
Числитель и знаменатель в дроби сокращаем на 13 и 2, тогда
х =1 * 4 * 1 / ( 1 * 3 * 1 * 3 )
х = 4 / ( 3 * 3 )
х = 4 / 9
ответ: х = 4 /
Пошаговое объяснение:
12,8=4×2,5+b
12,8=10+b
-b=10-12,8
-b=-2,8
b=2,8
ответ:b=2,8